To stand back or step in? Exploring the responses of employees who observe workplace bullying. Issue 1 (20th June 2017) - MacCurtain, Sarah; Murphy, Caroline; O'Sullivan, Michelle; MacMahon, Juliet; Turner, Tom
Abstract : Bullying remains a pervasive problem in healthcare, and evidence suggests systems in place are not utilised due to perceptions of ineffectiveness and inequity. This study examines bystander responses to bullying and factors that influence decisions to intervene. We explore relationships between bystanders' perceptions of psychological safety across three levels (organisation, supervisor and colleague) and reactions to witnessing bullying. We suggest psychological safety would be positively associated with the decision to intervene. Findings indicate the most pervasive reaction to witnessing incidents of bullying is to discuss with colleagues, a low‐involvement reaction. We find perceptions of supervisory and organisational safety/support are positively related to high‐involvement decisions such as formal reporting of the incidents, highlighting the importance of support from those in power. However, perceptions of collegial support may lead to low‐involvement responses, which risk reinforcing and underpinning dysfunctional organisational dynamics by providing informal social and emotional responses that may substitute more formal organisational responses to this persistent problem. This study highlights the importance of support from individuals in power if bystanders are to feel comfortable making high‐involvement interventions.